The development of decision support system for the selection of wastewater treatment process and plant design - 394049 Fadzlin Md. Sairan; Zaini Ujang, supervisor (Skudai : Universiti Teknologi Malaysia, 2009)
Thesis (Sarjana Kejuruteraan (Awam - Alam sekitar)) - Fakulti Kejuruteraan Awam, Universiti Teknologi Malaysia,2009